PERBANDINGAN HASIL SIMULASI SISTEM ROYALTI MINERAL EMAS TERHADAP PENERIMAAN NEGARA DAN RASIO KEUANGAN - SEDARTA
Abstract : Indonesia has ever been applying ad valorem and flat rate royalties. Especially for gold mining, ad valorem had been applied in 4th generation COW in which the rate was 1-2%. Flat rate was applied in further generations until the end of 1999. The royalty rate was $225-$335/kg. To increase government income from mining sector, Indonesian government enacted government regulation No. 13 of 2000 (called PP 13/2000) regarding amendment of PP 58/1998. Due to this regulation the type of royalty used is ad valorem with fixed rate. The rate is 3,75%, and it is larger than the royalty rates of 4th generation COW. A study is conducted to compare the 4th generation COW\'s royalty with the other types of royalty, e.g. base on PP 58/1998, PP 1312000 and, profit-based royalty with 3% and 12% rate. The criteria parameters are government income and company\'s financial ratio. The result of simulation: ? By applying PP 13/2000, government income will be larger 6,37%. By applying of PP 58/1998, government income will be larger 3,48%. By applying profit based 12%, government income will be larger 3,84%. ? All royalty systems will not evoke company\'s financial ratio that significantly difference. ? The financial ratio having highest effect was current ratio. By applying PP 13/2000, current ratio decrease 17,7%. By applying PP 5811998, current ratio decrease 6,5%. By applying profit based 12% current ratio decrease 5,8%. ? Company\'s return on equity is lower than the average return on equity of . mining companies operating in Indonesia because of the lower interest-incurred.